The Role of the International Criminal Court in the Evolution of the Principles of International Criminal Law on the Crime of Genocide. - Shehata, Mohamed (Journal of Legal Sciences, 2026)
Genocide,‍‌‍‍‌‍‌‍‍‌ as the most extreme form of destruction of human groups, has been one of the major threats to international law and its structures, peace, and security throughout history. The​‍​‌‍​‍‌​‍​‌‍​‍‌ global community has been seeking a legal framework for the punishment of the offenders and the assurance of non-repetition of such crimes since the 1948 Genocide Convention. The establishment of the International Criminal Court (ICC) by the 1998 Rome Statute was a significant moment in the system of international criminal law, particularly in the areas of specifying genocide, setting the evidential standards and clarifying individual criminal ​‍​‌‍​‍‌​‍​‌‍​‍‌responsibility. This study examines the ICC’s influence and reviews the landmark cases in Darfur and Myanmar. It also considers their legal and theoretical impact on the evolution of genocide law. Besides, the research discusses the issues of the ICC’s legality and politics in the case of genocide trials. The problems discussed are proving the case, getting international cooperation, and the resistance of some governments to participate. By means of a comparative analysis, the paper proposes various measures through which the Court could be more effective in the prevention of genocide, thus international justice and human dignity would be ‍‌‍‍‌‍‌‍‍‌furthered.